Case Report: Convalescent Plasma, a Targeted Therapy for Patients with CVID and Severe COVID-19 - Van Damme, Karel F. A.; Tavernier, Simon; Van Roy, Nele; De Leeuw, Elisabeth; Declercq, Jozefien; Bosteels, Cédric; Maes, Bastiaan; De Bruyne, Marieke; Bogaert, Delfien; Bosteels, Victor; Hoste, Levi; Naesens, Leslie; et al. (Frontiers in Immunology, 2020)
The disease course of COVID-19 in patients with immunodeficiencies is unclear, as well as the optimal therapeutic strategy. We report a case of a 37-year old male with common variable immunodeficiency disorder and a severe SARS-CoV-2 infection. After administration of convalescent plasma, the patient’s condition improved rapidly. Despite clinical recovery, viral RNA remained detectable up to 60 days after onset of symptoms. We propose that convalescent plasma might be considered as a treatment option in patients with CVID and severe COVID-19. In addition, in patients with immunodeficiencies, a different clinical course is possible, with prolonged viral shedding.